Determination of signal level for protection of information in case of its interception by technical means of intelligence - Pavlenko, Yevhen (Technology audit and production reserves, 2023)
The object of the current paper is the protection of information in the conditions of its interception by technical means of intelligence. According to this goal, considered the existing mathematical model of signal interception using radio-technical intelligence. In course of investigation, for getting final results based existing mathematical model analyzed the optimal scheme of signal detection with the help of intelligence receiver. As a result of this activity occurs four potential cases of signal detection which compared with established threshold H and accompanied by one of two error types: incorrect decision about the signal absence or incorrect indication of its presence. On the basis of the given cases suggested one of the possible variant for protecting of signal that goes beyond the controlled zone. Using such dependencies as: an expression of the power flux density of radio electronic device antenna on its distance to the receiver in the direction of maximum radiation, the formula of signal power at the input of the receiving antenna, the ratio of the antennas coefficient of amplification and its effective scattering area was obtained: the dependence for calculating the power of output signal sufficient for reception within the controlled zone, but insufficient for its interception by technical means beyond its borders. Also, obtained graphical dependencies of minimal coefficient of amplification of transmitter antenna from maximal coefficient of amplification of transmitter antenna, from wavelength of radiation and from distance between transmitter and receiver. Based on research results formed the conclusion regarding proposed method of information protection based on the mathematical model of the information leakage channel applying for radio intelligence.